Age differences on communication styles among married adults in Oyo state, Nigeria - Ruth Adesokan; Alfred H. Makura; Mary O. Esere (International Journal of Studies in Psychology)
The study examined the impact of age differences in married adults' communication styles in Oyo state, Nigeria. It adopted a quantitative approach and a descriptive survey research design. The multi-stage sampling technique randomly selected six hundred (N=600) married adults. The questionnaires were used for data collection in this study, and the respondents were required to use four points Likert rating scale. The experts in Counsellor Education Department at the University of Ilorin validated the instrument. Mean, Standard Deviation, and Analysis of Variance were employed as data analysis techniques. The findings revealed that married adults mostly adopted the marital communication styles, which tended more towards the supportive style. The results further indicated that age has an insignificant impact on the communication styles of married adults. It is recommended that married adults adopt a supportive communication style to promote understanding, openness, empathy, adaptability, and cooperation between them and their spouses.